Publicistic Opportunities - Docent B.B.Rahimova; Sh.Isakjanova (Zien Journals, 2022)
In this article we will talk about the publicistic activity of the creator Sirojiddin Sayyid. Some of his articles give examples of the poet's publicistic views
Keywords: publitsistics; essay; social reality; artistic image